1978
DOI: 10.1098/rsta.1978.0020
|View full text |Cite
|
Sign up to set email alerts
|

The wakes of cylindrical bluff bodies at low Reynolds number

Abstract: Experiments on the near wake of a cylinder will be discribed in an attempt to present a coherent picture of the events encountered as the Reynolds number increases from small values up to values of a few thousand. Much work on this subject has already been done, but there are gaps in our description of these flows as well as more fundamental deficiencies in our understanding of them. The subject has been reviewed several times and most recently by Berger & Wille (1972) whose paper covers much of the ground… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
70
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 286 publications
(72 citation statements)
references
References 29 publications
2
70
0
Order By: Relevance
“…It is noted that all vortices except the ones that follow UT 2 further upstream and 0.25D higher as compared to those of UT 2 . They go upwards until x/D ≈ 4 and then downwards until they reach the trajectory UT 2 .…”
Section: A Spanwise Vorticesmentioning
confidence: 98%
See 1 more Smart Citation
“…It is noted that all vortices except the ones that follow UT 2 further upstream and 0.25D higher as compared to those of UT 2 . They go upwards until x/D ≈ 4 and then downwards until they reach the trajectory UT 2 .…”
Section: A Spanwise Vorticesmentioning
confidence: 98%
“…A lot of effort was made to explain the physics of circular cylinder wake dynamics. [1][2][3] They showed that vortex shedding for low Reynolds numbers can be characterized by vortex splitting and high shear stress occurring in the near-wake. Unal and Rockwell 4 investigated the near wake vortex formation from the context of absolute instability and showed that the shear layer separating from the cylinder shows an exponential variation of fluctuating kinetic energy with distance downstream of the cylinder.…”
Section: Introductionmentioning
confidence: 99%
“…The exact Reynolds number at which vortex shedding begins depends on the flow conditions. For a laterally uniform upstream velocity, the transition occurs at Re, = 60 (Gerrard 1978). However, in the presence of shear the transition may be delayed to Re, = 200 (Tamura et al 1980).…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…A visualization of Hama 4 showed that the instability in the wake transition takes the form of a three-dimensional waviness of the von Kármán vortices. This is essentially what Gerrard 5 later called ''fingers of dye.'' Williamson's flow visualization 6 showed that Gerrard's dye fingers are associated with vortex loops and streamwise vortices.…”
Section: Introductionmentioning
confidence: 99%